PARTICIPATION OF MUSLIM COMMUNITY VILLAGE IN ENTERPRISE MANAGEMENT OF VILLAGE OWNED ENTERPRISE IN INDONESIA - Heru Dian Setiawan (Jurnal Sosiologi Reflektif, 2018)
The establishment of a Village Owned Enterprise (BUMDes) as stipulated in Law No.6 / 2014 on Village, is an effort to increase economic growth along with equitable distribution of assets to the people in order to be able to cope with various economic problems in rural areas. However, since the BUMDes policy was established (in 2004), the existence of BUMDes has not been fully satisfactory, as only about 9.09% of villages realize BUMDes program, even from the number of presentations there are only 21.68% BUMDes considered profitable. Many factors influence the development and development of BUMDes program. One of the most important factors is the lack of social capital development in rural areas. This implicitly indicates the lack of participation of the largest and most important social capital that Indonesia has in the village Muslim community in the management of BUMDes. Yet this village Muslim community as an important asset to further create opportunities to improve rural economic welfare through the utilization and management of BUMDes in Indonesia. Therefore, the qualitative descriptive qualitative study aims to analyze the factors that influence the participation of the village Muslim community in the development and management of BUMDes in Indonesia, using the opinion of Korten which suggests that the success or failure of participation is grouped into two categories namely internal factors and factors externalTerbentuknya BUMDes sebagaimana tertuang dalam UU No.6/2014 belum sepenuhnya mampu menanggulangi berbagai permasalahan ekonomi di pedesaan, karena hanya sekitar 9,09% desa yang dinilai mampu 396  merealisasikan program BUMDes, bahkan dari jumlah prosentase tersebut hanya terdapat sekitar 21,68% BUMDes yang dinilai menguntungkan. Banyak faktor yang mempengaruhi ketidakberhasilan pembangunan program BUMDes. Satu faktor paling penting adalah kurangnya pengembangan modal sosial di pedesaan. Secara implisit ini menandakan rendahnya partisipasi modal sosial terbesar dan terpenting yang dipunyai Indonesia yaitu komunitas muslim desa. Untuk itu, kajian yang berproses deskriptif kualitatif ini bertujuan untuk menganalisis faktor-faktor yang mempengaruhi partisipasi komunitas muslim desa dalam usaha pengelolaan BUMDes di Indonesia, dengan menggunakan pendapat Korten yang mengemukakan bahwa kesuksesan atau kegagalan partisipasi dikelompokkan dalam dua kategori yakni faktor internal dan faktor eksternal.Keywords: Participation, Muslim Village Community, Village Owned Enterprise Management, Village Owned Enterprise.